Effect of electrolysed water on Campylobacter numbers on poultry carcasses under practical operating conditions at processing plants. (April 2015) - Burfoot, Dean; Mulvey, Elizabeth; Jewell, Keith; Foy, Emma; Howell, Mary
Abstract: This study investigated the effectiveness of spraying electrolysed water for reducing the numbers of Campylobacter on chicken carcasses. Previous studies have used solutions with free chlorine concentrations above 25 ppm and low pH to treat inoculated carcasses. The four trials described here were carried out at process plants treating naturally contaminated, hot, birds with electrolysed sodium chloride or sodium carbonate solutions, plain water, or no water. The birds were chilled after treatment. Free chlorine concentrations were all below 20 ppm, pH was 7 units or more, and redox potentials were below 830 mV. None of the treatments produced more than a 0.3-log reduction in Campylobacter numbers compared to counts on untreated carcasses. This study concludes that, at the low chlorine concentrations allowed in the EU, spraying with electrolysed water is not an effective method of reducing the number or prevalence of Campylobacter on chicken carcasses. Highlights: Carcasses were treated with an electrolysed water, plain water or no water. Free chlorine concentrations were below 20 ppm. None of the treatments produced more than a 0.3-log reduction in Campylobacter .